DOMINANSI DAN POLA ZONASI MANGROVE DI DESA PENTADU BARAT TELUK TOMINI GORONTALO - Rahim, Ditya Nanda; Kasim, Faizal; Nane, La (Coastal and Ocean Journal (COJ), 2024)
The purpose of this study is to discover the composition, dominance index value, and zoning pattern of mangrove plant in Pentadu Barat Village, Tilamuta Subdistrict, Boalemo Regency. This study was conducted from January to March 2023. The sampling method is purposive sampling using 10 × 10 cm linear transect for tree, 5 × 5 cm linear transect for saplings, and 2.5 × 2.5 cm linear transect for seedlings. The mangrove sample is descriptively and quantitatively analysed by identifying the species to calculate the type compositions and dominance index using Microsoft Excel. The result of the study reveals 12 species of 4 families from 3 study location (Avicennia alba, Avicennia officinalis, Bruguiera cylindrical, Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops decandraCeriops tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba and Xylocarpus granatum). The type composition value was 35% from Rhizophora mucronata. The average dominance index value was 0.0174. The zoning pattern was mixedbecause it grows mixed with each other among several species.